2015
DOI: 10.1093/emph/eov021
|View full text |Cite
|
Sign up to set email alerts
|

Diametrical diseases reflect evolutionary-genetic tradeoffs

Abstract: Tradeoffs centrally mediate the expression of human adaptations. We propose that tradeoffs also influence the prevalence and forms of human maladaptation manifest in disease. By this logic, increased risk for one set of diseases commonly engenders decreased risk for another, diametric, set of diseases. We describe evidence for such diametric sets of diseases from epidemiological, genetic and molecular studies in four clinical domains: (i) psychiatry (autism vs psychotic-affective conditions), (ii) rheumatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 422 publications
(275 reference statements)
1
34
0
Order By: Relevance
“…Probably not, because technical expertise usually comes with costs in social skills that would stymie social transmission. Indeed, "folk physics" shows clear evidence of tradeoffs with "folk psychology" (Baron-Cohen 2000; Baron-Cohen et al 2001), technical and visual-spatial skills trade off with social abilities more generally in autistic as well as non-autistic individuals (Crespi & Go 2015 , Table 1), and autism is well known to engender reductions in ability and/or motivation to imitate, emulate, innovate, engage in joint attention, and, most broadly, enculturate (e.g., Baron-Cohen 1993;Charman 2003;Colombi et al 2009). The existence of such tradeoffs vitiates the direct connection of technical reasoning with imitation and innovation posited by O&R as key to their model.…”
Section: Introductionmentioning
confidence: 99%
“…Probably not, because technical expertise usually comes with costs in social skills that would stymie social transmission. Indeed, "folk physics" shows clear evidence of tradeoffs with "folk psychology" (Baron-Cohen 2000; Baron-Cohen et al 2001), technical and visual-spatial skills trade off with social abilities more generally in autistic as well as non-autistic individuals (Crespi & Go 2015 , Table 1), and autism is well known to engender reductions in ability and/or motivation to imitate, emulate, innovate, engage in joint attention, and, most broadly, enculturate (e.g., Baron-Cohen 1993;Charman 2003;Colombi et al 2009). The existence of such tradeoffs vitiates the direct connection of technical reasoning with imitation and innovation posited by O&R as key to their model.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, tradeoffs occur when a trait cannot increase without a decrease in another one and it has been supposed that beneficial genotypes may pleiotropically generate deleterious effects in phenotypes that trade off with them. This concept has been proposed for many diseases, such as cancer, neurodegeneration, autoimmune and infectious diseases [ 9 ]. It has been also suggested that an evolutionary approach that relies on models/assumptions of population genetics may help in predicting the genetic background of susceptibility to such diseases [ 6 , 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter may explain the reported association of 8.1 AH with protection against infectious events . By conferring susceptibility to autoimmune disorders on one hand and protection against infections on the other, the 8.1 AH can be considered as a prototypic example of evolutionary‐genetic trade‐offs in conferring diametric disease risks further influenced by genetic and environmental variations . Under the diametric model, the postulation is that the Initial pathogen‐driven pressure positively selects the 8.1 AH, which over time, when the pressure load diminishes, as of today, expresses its deleterious effect in terms of autoimmunity.…”
mentioning
confidence: 99%